207 Sociodemographic, Behavioral, and Health-Related Factors Associated with Sleep Among Native Hawaiians and Other Pacific Islanders. (3rd May 2021) - Barker, Madison; Gilles, Allyson; Ghani, Sadia; Killgore, William; Knowlden, Adam; Wills, Chloe; Grandner, Michael
Abstract: Introduction: Previous studies have suggested that Native Hawaiians/Pacific Islanders show different associations between sleep and health risks, compared to other groups. The present study evaluated sleep and health risk factors in a nationally-representative sample. Methods: Data from the Native Hawaiian and Pacific Islander National Health Interview Survey (NHPI-NHIS), collected by the CDC in 2013, was used for analysis. A total of N=2, 124 individuals provided complete data on all variables. Sleep outcomes included hours of sleep (3-12h), days/week difficulty falling asleep, difficulty maintaining sleep, and nonrestorative sleep (ordinal). Weighted regression analyses (linear or ordinal logistic) evaluated whether sleep outcomes were associated with cancer, diabetes, hypertension, stroke, obesity, poor health, depression, anxiety, smoking, alcohol, activity, functional limitations, foregoing medical care due to cost, frequent healthcare utilization, health insurance, and difficulty paying medical bills, in models that also included age, sex, immigrant status, multiracial status, education, employment, income, and relationship status. Results: Shorter sleep was associated with older age, earning <$20, 000, and being divorced/widowed/separated, and longer sleep was associated with being female and less than high school education. Shorter sleep was also associated with fair health and current drinking. Difficulty falling asleep was positively associated with older age, earning <=$44, 999, being divorced/widowed/separated, obesity, worse health, depressed mood, anxiety, daily smoking, former and current drinking, functional limitations, foregoing care, frequent care, and difficulty with bills. Difficulty falling asleep was negatively associated with immigrant status and being retired. Difficulty maintaining sleep was associated with older age, being unmarried but partnered, obesity, worse health, depression, anxiety, daily smoking, current or heavy drinking, being inactive, functional limitations, foregoing care, frequent care, and difficulty with medical bills. Nonrestorative sleep was associated with non-immigrant status, employment, being a homemaker, disability, being unmarried, obesity, worse health, depression, anxiety, daily smoking, former, current, or heavy drinking, inactivity, functional limitations, foregoing care, frequent care, and difficulty with medical bills. Conclusion: Short sleep was not significantly associated with common health risk factors seen in other groups. Sleep difficulties, though, were related to a constellation of sociodemographic, socioeconomic, behavioral, and cardiometabolic risks. Further research regarding insomnia as a health risk factor in this population is warranted. Support (if any): R01MD011600, R01DA051321